Transformasi Nilai-Nilai Ajaran Islam melalui Pewayangan - Huda, Fatakhul (Fakultas Dakwah Intitut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2023)
ABSTRAK Wayang is the most complete literary work, meaning that wayang itself contains many artistic elements, such as: painting, sculpture, dance, drama, sound and music. Not only that, as has been mentioned above, in fiber wayang there is a philosophy of life which is reflected in all elements of wayang, both in the form of wayang, wayang characters, gamelan music, and other symbols such as mountains, all of which are certainly not the result of literary works. origin, but a creative process that requires deep thought. Apart from schools and families, wayang art can be used as a medium to transform the values ​​of Islamic teachings, because in its wayang performances it always carries a moral message to the people who see it. In simple wayang, opinions can be expressed about humans with their life goals, ideals, and behavior, besides all their beauty, wayang always provides its own charm, with musical accompaniment and the puppeteer's flexibility in dancing beautiful wayang puppets, making wayang a medium for preaching which is still popular with Javanese people in general.